A bottom-up selection algorithm for configuration design - Shuck, Chin Leong. (2009)
This dissertation describes a bottom-up configuration design algorithm. A configuration system constructs a design from a fixed set of components which may be stored in a library or given as inputs. The bottom-up approach selects individual components to form sub-assemblies which are then arranged to configure a complete product. A bottom-up approach algorithm has been developed to configure modular units of factory automation equipment in this project. The algorithm has been implemented using the Autolisp® language and the Windows version Autocad® Release 12 program.